Manejo del dolor agudo pos quirúrgico - Poggi Machuca, Luis (2024)
The present article on acute postsurgical pain reviews the positive and negative effects of pain, in the short and long terms, in surgical patients; describes the diverse types of pain according to their physiopathology, and the use of the various types of analgesic pharmaceuticals, such as the opioids, non steroidal anti-inflammatory drugs (NSAIDs) and local anesthetics. The indications and contraindications of analgesia with opioids and subcutaneous analgesia, as well as appropriate precautions and adverse effects are described. The subjects of patient controlled analgesia (PCA), and continuous epidural analgesia (CEA) are discussed. On comparing these two methods, it was possible to conclude that the latter one, continuous epidural analgesia, was better than PCA in the first 72 hours of pain management. Finally the diverse conventional postoperative pain therapies are reviewed, multimodal therapy and sequential therapy.